Telurooxetanas: estudos cristalográficos, modelagem molecular e cálculos de docking para aplicação biológica - Maganhi, Stella Hernandez (2009)
This work is composed of 4 chapters. In Chapter 1 is a description of the problems addressed here, starting with the characteristics of the protein, its biological and social importance, and the interactions responsible for both its structure and the formation of ligand-protein complexes, there is also a brief description of Te(IV) compounds followed by the presentation of the grounds of the experimental methods used, namely crystallography and docking. In Chapter 2 the objectives of this work are presented. Chapter 3 includes the experimental procedures that were used to determine the crystal and molecular structures, the modeling of the compounds that did not have crystallographic structure, as well as the molecular docking. In Chapter 4 are described and discussed the results. The crystal structures of the telluroxetanes (3E)-2-chloro-3-(chloromethylidene)-2-(4- methoxyphenyl)-1-oxa-2 λ4- telluraspiro[3.6]decane (1) and of (3E)-2-chloro-3-(chloromethylidene)-2-(4- methoxyphenyl)-1-oxa-2 λ4- telluraspiro[3.5]nonane (2) show that the coordination polyhedron around the atom of Te is a pseudo-pentagonal bipyramid. The supramolecular synthon is different in the two cases, in spite that the Te atom makes a secondary interaction with a halide, in both cases. The docking results for all tellurium compounds have shown that these ligands form complexes with Cathepsin B through the formation of a covalent bond between the Te and S of Cys29 of the enzyme. The differences in the values of scores from the docking and the number of interactions are due, mainly, the size of the carbon chain. Finally the conclusions and outlook can be found.